Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Belanja Daerah Kabupaten Mamberamo Tengah Tahun 2014-2023 - Silas Isir; Risky Novan Ngutra (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2024)
This study aims to analyze the effectiveness level of Local Own-Source Revenue (PAD), Balance Funds, and Regional Expenditure, as well as to examine the partial and simultaneous effects of PAD and Balance Funds on Regional Expenditure in Central Mamberamo District from 2014 to 2023. The research uses secondary data from the Regional Financial and Asset Management Agency and applies effectiveness ratio analysis and multiple linear regression with SPSS. The results show that PAD effectiveness remains low and fluctuating, with no year achieving the effective category. In contrast, Balance Funds effectiveness improved consistently from less effective to effective in recent years. Regional Expenditure effectiveness is generally stable and effective. The regression analysis reveals that partially, PAD has a positive and significant effect on Regional Expenditure, while Balance Funds do not. However, simultaneously, both variables significantly affect Regional Expenditure. The study concludes that PAD plays a more dominant role than Balance Funds in influencing Regional Expenditure. The local government is advised to optimize PAD collection and allocate Balance Funds more productively to enhance regional financial independence. Keywords: Local Own-Source Revenue, Balance Funds, Regional Expenditure, Effectiveness, Multiple Linear Regression, Central Mamberamo